Madin Inovatif: Pendampingan Mahasiswa Madrasah Diniyah Dalam Menyusun Dan Menerbitkan Artikel Ilmiah Berbasis Pendidikan Terindeks SINTA - Sufinatin Aisida; Farhat Muhammad; Adibah (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Publication of scientific papers is a form of embodiment of scientific work uploaded in one of the journals. The purpose of this service is to increase knowledge, understanding of assisted subjects about scientific works and publications, the formation of a community of scientific writers for assisted subjects and the creation of a culture of reading and scientific literacy that has a consistent impact on scientific publications. The method used in Community Service is the concept of service learning with stages: (1) investigation; (2) preparation; (3) actions; and (4). The results of this assistance show an increase in understanding of the installation delay and its application by 98%, understanding the structure of scientific articles and writing ethics by 85%, citation and anti-plagiarism by 80%, tutorials looking for journals and journal sections by 95% and SINTA journal submission tutorials, by 100%. The implementation of training and mentoring ran successfully according to the expectations that have been scheduled.